Eurobonds : A Quantitative Analysis of Joint-Liability Debt - Tsiropoulos, Vasileios (World Bank, Washington, DC, 2019)
This paper assesses the consequences of implementing a joint liability debt system in a two-country small open economy model. With joint liability a default of one country makes the other participant liable for its debt. The results highlight a trade-off between the contagion risk, in the sense that this instrument may push some member states to default even though they are individually solvent, and cheaper access to credit on average, since lenders are at risk only if no participating sovereign is willing to service the debt. The findings suggest that the welfare consequences of this policy proposal hinge critically on the timing of its introduction: Introducing such instruments at the peak of the Eurozone crisis would have helped the Periphery and harm the Core member states, while its adoption during normal times has the potential to make all participants better-off.